Precision laser therapy for retinoblastoma. (4th May 2018) - Soliman, Sameh; Kletke, Stephanie; Roelofs, Kelsey; VandenHoven, Cynthia; Mckeen, Leslie; Gallie, Brenda
ABSTRACT: Introduction : Laser therapy is a cornerstone for control of intraocular retinoblastoma, after chemotherapy has brought the disease under initial control. Since first described over 6 decades ago, laser technologies and approaches have evolved to improve tumor control. Despite its important role, few publications describe techniques, types of lasers, and modes of delivery for retinoblastoma. Areas covered : The physical and optical properties of lasers, mechanisms of action, delivery systems and complications are described. Hand-held optical coherence tomography (OCT) detects microscopic retinoblastoma tumors and guides treatment, achieving precision primary therapy and elimination of recurrences. Expert commentary : In all the excitement of new therapies to cure intraocular retinoblastoma, laser treatment always compliments but is rarely mentioned. Hand-held OCT now adds precision to put laser in the forefront in achieving cure of retinoblastoma.